Marketing Strategy for Hajj Savings at Bank Muamalat in Medan within the Framework of Sharia Economic Law - Tsabitah Fadlilah Batubara; Uswah Hasanah (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
This study aims to analyze the marketing strategy for Hajj savings implemented by Bank Muamalat in Medan within the framework of Sharia Economic Law. The research uses a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. The analysis emphasizes sharia principles, particularly related to the application of wadiah and mudharabah contracts and the importance of transparency in Hajj savings products. Findings indicate that Bank Muamalat applies a multi-dimensional marketing strategy, including public education on the advantages of iB Hajj Savings, the use of digital platforms such as BMI Mobile to facilitate registration and transactions, and the implementation of promotional programs such as cashback and direct prizes that avoid gharar and riba. These efforts have led to a significant increase in Hajj portion acquisition and customer interest in Sharia-compliant savings products. This study highlights how compliance with fatwas issued by the National Sharia Council (DSN-MUI) and regulations from the Hajj Financial Management Agency (BPKH) strengthens public trust in Islamic financial services. Academically, this research contributes to the development of Islamic financial marketing strategies that align with legal and ethical standards in Islamic economic law, particularly in the marketing of religious financial products such as Hajj savings.Keywords: Sharia Economic Law; Hajj Savings; Islamic Marketing; Bank Muamalat; Fatwa Compliance